2010
DOI: 10.1037/a0018699
|View full text |Cite
|
Sign up to set email alerts
|

Physiological down-regulation and positive emotion in marital interaction.

Abstract: Previous studies have demonstrated that 1 function of positive emotion is the undoing of physiological arousal produced by negative emotions. These studies have used single-subject paradigms, in which emotions were induced by films in college-age individuals. In the present study, we examined the relationship between physiological down-regulation and positive emotion in a sample of 149 middle-aged and older married couples engaged in a 15-min discussion of an area of marital conflict. During the conversation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 59 publications
3
53
0
Order By: Relevance
“…A far smaller number of studies have measured emotion regulation in interpersonal contexts (e.g., Butler et al, 2003; Yuan, McCarthy, Holley, & Levenson, 2010). Single subject paradigms using standardized emotional stimuli afford good experimental control, but they cannot capture the rich interpersonal dynamics that define the contexts in which most emotion regulation occurs (Aldao, 2013; Coan, 2008; Diamond & Aspinwall, 2003; Levenson et al, in press).…”
Section: Emotion Regulation Predicts Marital Satisfaction: More Than mentioning
confidence: 99%
“…A far smaller number of studies have measured emotion regulation in interpersonal contexts (e.g., Butler et al, 2003; Yuan, McCarthy, Holley, & Levenson, 2010). Single subject paradigms using standardized emotional stimuli afford good experimental control, but they cannot capture the rich interpersonal dynamics that define the contexts in which most emotion regulation occurs (Aldao, 2013; Coan, 2008; Diamond & Aspinwall, 2003; Levenson et al, in press).…”
Section: Emotion Regulation Predicts Marital Satisfaction: More Than mentioning
confidence: 99%
“…Indeed, Fredrickson and Levenson [10] showed that cardiovascular activity induced by watching a negative film returns to baseline more quickly after watching a cheerful film than after a sad or neutral film. The undoing effect has been observed for visual images that elicit contentment and amusement following a fear-eliciting film [11], for pleasant pictures following unpleasant pictures [12], for pleasant music following disgusting pictures [13], and during a dyadic marital interaction with positive emotional behaviors [14]. …”
Section: Introductionmentioning
confidence: 99%
“…We consider reward laughter to be rewarding to the producer and recipient. 2 Producing laughter is inherently enjoyable (Herring, Burleson, Roberts, & Devine, 2011;Mauss, Levenson, McCarter, Wilhelm, & Gross, 2005) and down-regulates negative emotions (Bloch, Haase, & Levenson, 2014;Keltner & Bonanno, 1997;Yuan, McCarthy, Holley, & Levenson, 2010). Laughing triggers the release of opioids in the brain, providing direct evidence of its rewarding value (Dunbar et al, 2012;Manninen et al, 2017).…”
Section: Reward Laughter: Reinforcing Behaviors and Social Bondsmentioning
confidence: 99%